Combination of Spent Mushroom Substrate and other Agricultural By-products in Compost Production - Pham, Nhung Thi Ha (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 1SDO - 10.25073/2588-1094/vnuees.4132, 2017)
Although spent mushroom substrate (SMS) is one of the factors causing pollution for mushroom production area, SMS is a nutrient-rich organic material which can be used for compost production, especially when it combines with other agricultural by-products. The analysis results show that pH (7.22-7.87) and moisture (60.20-73.28%.) of compost products made from all formulas are suitable for many types of crop, particularly, organic matter content is very high in formula 1 (CT1) with 72.20%, formula 3 (CT3) with 61.94% and the lowest value is 27.62%at formula 5 (CT5). Total nitrogen content reaches the highest value at the CT1 (0.58%), following is formula 2 (CT2)at 0.55%, and the CT5 has the lowest content with 0.25%; Total phosphorus content, which is relatively low, merely obtains 0.35% in control formula, 0.22% at the CT2 and the lowest point is 0.15% at the CT5; Total potassium contents are quite equal, in which, the CT5 has the highest value with 0.80% and formula 4 has the lowest value with 0.46%. The research also indicates thatnutrient norms of the products from mixed formulas with stalks and leaves of maize, peanut and kudzu (CT1, CT2 and CT3) are better than those from the remain formulas. However, with the pak choi planting experiments,only composts from the CT1 and the CT3 make optimal conditions for the growth of plants while pak choi in experiment with the product from the CT2 is less developed than plant in experiments with other products. Thus, the combination of maize stalks and leaves, and SMS in compost production gives huge potential in enhancement of product quality after treament, as well as reduces the risk of pollution from agricultural by-products.